Virtual reality in the rehabilitation of patients with stroke: an integrative review - Aramaki, Alberto Luiz; Sampaio, Rosana Ferreira; Reis, Ana Caroline Silva; Cavalcanti, Alessandra; Dutra, Fabiana Caetano Martins Silva e (Arquivos de Neuro-Psiquiatria, 2019)
Objective: To describe the intervention protocols to using commercial video games as virtual reality (VR) in rehabilitation of patients with stroke.Methods: Integrative review using the descriptors “rehabilitation”, “virtual reality exposure therapy” and “videogames” in the LILACS and PUBMED databases. Articles published from 2011 to 2018 were selected.Results: We found 1,396 articles, 1,383 were excluded and 13 were selected. Most of the articles were randomized clinical trials published in 2014 or later. The sample size varied from 5–47 adults, or adults and elders, with chronic stroke. The Nintendo Wii® was the most used video game system. The intervention happened two or three times a week, each session lasting from 30 to 60 minutes, over 2–12 weeks. Balance, upper limb motor functions, quality of life and daily living activities were the most common evaluated outcomes. The Fugl-Meyer Assessment, Berg Balance Scale, Timed Up and Go test, Barthel Scale and SF-36 were the most common outcome measurement tools.Conclusions: The studies indicated improvement in dynamic balance, upper limb motor function and quality of life after rehabilitation using VR. The VR was more effective than conventional treatments for the outcome of dynamic balance. Two studies did not find any changes in static balance and daily living activities. Physical aspects and quality of life were the outcomes most evaluated by the researchers; as were the population with chronic strokes and protocols of long duration and low intensity. Few studies targeted immediate VR effects, performance in daily living activities and social participation.
Keywords: Rehabilitation; virtual reality exposure therapy; video games; stroke